Answer:
9
Step-by-step explanation:
You gave the answer right in your question
Answer:
(4,11)
Step-by-step explanation:
y=2x+3
y=5x-9
the first equation is equal to the second equation so
2x+3=5x-9
put like terms together
2x-5x= -9-3
-3x= -12
divide both sides by -3
.•.x=4
now, use the value of x to find the value of y like this:
y=2x+3 (x=4)
y=2(4)+3
y=8+3
y=11
therefore, the two lines intersect at the point (4,11)
<span>17 1/3 + (-50 1/3) -5 1/2
= -33 - 5 1/2
= (</span>-33 ) + ( - 5 1/2)
<span>= -38 1/2
</span>
Force = mass * acceleration
Mass = force / acceleration
Mass = 55.54 / 9.83
Mass =
<span>
<span>
<span>
5.6500508647 kilograms
</span></span></span>Mass =
<span>
<span>
<span>
5.65 kilograms
</span></span></span>
The answer to the question is: Yes.
Explanation: It can be solved by following exactly the same procedures
that solved the other two questions that you posted within the past 15 minutes.
Since I'm here already, here is the solution to this one:
6x² + 18x = 0
Divide each side of the equation by 6 :
x² + 3x = 0
Factor the left side:
x(x+ 3) = 0
This statement is true if x=0 or if x=3.
The solution to this one is even the same as the solution to the last one you posted.
You really ought to take a break, go back, review the solutions you've been given,
and try to solve a few on your own.